Distribution and diversity of aquatic macrophytes and the assessment of physico-chemical parameters of Dakatia beel in Khulna district, Bangladesh (Asian Journal of Medical and Biological Research, 2021)
The physico-chemical characteristics of water and aquatic macrophytes from Dakatia Beel under Khulna district in Bangladesh were studied within January, 2020 to February, 2021. Twenty three species of aquatic macrophytes belonging to 15 families have been recorded. The aquatic macrophytes in Dakatia Beel collected from several sites belonging to 23 genera and 15 families (Lemnaceae, Pontederiaceae, Araceae, Convolvulaceae, Amaranthaceae, Asteraceae, Fabaceae, Polygonaceae, Ceratophyllaceae, Onagraceae, Parkeriaceae, Cyperaceae, Poaceae, Euphorbiacee, Nymphaceae). We also observed the different plant groups which comprises 6 species of floating, 10 species of emergent and only 2 species of submerged aquatic macrophytes. Dissolved oxygen ranged between 1.78 to 2.2 mg/L with a mean value 1.95 mg/L. The study area showed maximum total dissolved solid 588 ppm and the minimum in 482 ppm with a mean value of 534 ppm. Maximum value of phosphate was noted in 1029 μg/L and minimum 988 μg/L with a mean value of 1005 μg/L.Asian J. Med. Biol. Res. 2021, 7 (2), 118-125